Voices from the Front Line: Young People Interrogating Railton Road's Heritage. (3rd July 2019) - Mullings-Lawrence, Sireita
Abstract: One of the ways in which we have come to make sense of our social positions and give context to our role in local and global society is by way of an engagement with the photograph. As a means to log events and moments that are key to enabling an interaction with a community's cultural heritage, the visual as a space for encounter and exchange facilitates not only a photographic dialogue but also the opening up of a network that allows for the components of heritage to be accessed. This article explores the process and methods employed during a participatory youth and community arts project, Voices from the Front Line, that draws upon visual heritage and sought to move beyond the preservation of objects as archives. It will interrogate the use of the visual as a nonlinear framework to engage young people in their community heritage by way of unraveling the political and social history of Brixton's Railton Road. Engaging with visual heritage, young people's artistic responses to relevant public archives opened up a discussion about the types of encounters and exchanges that occurred during the project process.